2004
DOI: 10.1007/s00464-003-9170-1
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open total mesorectal excision with anal sphincter preservation for low rectal cancer

Abstract: Totally laparoscopic TME with ASP is feasible, and it is a minimally invasive technique with the benefits of much less blood loss during operation, earlier return of bowel function, and shorter hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
249
1
29

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 268 publications
(290 citation statements)
references
References 34 publications
(35 reference statements)
11
249
1
29
Order By: Relevance
“…Despite this, the better short term recovery of the LAC group could be demonstrated by the fewer days spent in the ICU and shorter hospital stay. This has been demonstrated in most of the other series as well [5,[10][11][12][13][14]16].…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Despite this, the better short term recovery of the LAC group could be demonstrated by the fewer days spent in the ICU and shorter hospital stay. This has been demonstrated in most of the other series as well [5,[10][11][12][13][14]16].…”
Section: Resultsmentioning
confidence: 56%
“…This is reflected by the fact that many large multicenter trials except MRC-CLASSIC have not included patients with rectal cancer [9]. However, there are 5 randomized trials published till date and that have demonstrated comparable short term outcome of laparoscopic and open surgery [4,6,[9][10][11][12][13][14][15]. Our study also shows comparable short term outcome of the LAC group with relatively early recovery following surgery.…”
Section: Resultsmentioning
confidence: 63%
“…It is important is to preserve the parasympathetic sacral nerve roots from S2 to S4. Dissection proceeds down to the pelvic floor [75][76][77][78][79][80][81][82][83][84][85][86][87][88].…”
Section: (100% [Strong Consensus]; Gor C: 100% [Strong Consensus])mentioning
confidence: 99%
“…The rectum is transected at the level of the pelvic floor by means of a roticulating endostapler device [75][76][77][78][79][80][81][82][83][84][85][86][87][88], using as few cartridges as possible. Use of more than two cartridges has been reported to result in a higher anastomotic leakage rate [89,90].…”
Section: (100% [Strong Consensus]; Gorb: 100% [Strong Consensus])mentioning
confidence: 99%
See 1 more Smart Citation